2023
DOI: 10.1039/d2fo04092a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of synbiotic milk powder and its effect on calcium absorption and the bone microstructure in calcium deficient mice

Abstract: Synbiotic milk powder improves the bone state of calcium-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The number of viable probiotic bacteria was significantly increased by adding prebiotics and the synbiotic product improved calcium absorption in calciumdeficient mice followed by increased serum calcium and phosphorus levels and bone mineral density. 93 Lactobacillus paracasei addition in milk powder exhibits a preventive effect on dental caries by inhibiting the growth of mutans streptococci and increasing salivary IgA. 94 Many plant-based products are high in fibres that naturally serve as prebiotics and may be rich in other beneficial compounds such as phenolic compounds.…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of viable probiotic bacteria was significantly increased by adding prebiotics and the synbiotic product improved calcium absorption in calciumdeficient mice followed by increased serum calcium and phosphorus levels and bone mineral density. 93 Lactobacillus paracasei addition in milk powder exhibits a preventive effect on dental caries by inhibiting the growth of mutans streptococci and increasing salivary IgA. 94 Many plant-based products are high in fibres that naturally serve as prebiotics and may be rich in other beneficial compounds such as phenolic compounds.…”
Section: Probioticsmentioning
confidence: 99%
“…9 As for products in instant powder forms, the health benefits of skimmed milk powder containing Lactobacillus plantarum on overweight adults have been evaluated by Rahayu, et al (2021) 8 and a significant reduction in body weight and body mass index were observed. Jia, et al (2023) 93 has developed synbiotic milk powder fortified with protein, minerals, vitamins, Lactobacillus plantarum and isomaltooligosaccharide. The number of viable probiotic bacteria was significantly increased by adding prebiotics and the synbiotic product improved calcium absorption in calcium-deficient mice followed by increased serum calcium and phosphorus levels and bone mineral density.…”
Section: Potential For Health Benefitsmentioning
confidence: 99%
“…HE staining of samples stained with hematoxylin and eosin can clearly identify the morphologic structure of tissues, which can play an auxiliary role in exploring the effects of DSPs-Ca on calcium absorption and bone deposition in mice. 54 Thus, the femur sections of the mice in each group were stained to observe the microstructure and growth of the bone. HE staining showed that the trabeculae of the bone samples in the NC group were coarse, tightly structured, neatly aligned, and had good continuity, showing a reticular distribution, whereas in the LC group, the degree of separation increased, the trabeculae were severely fractured, and the connecting interruptions of the trabeculae were markedly increased, with the trabeculae being sparsely distributed.…”
Section: Morphological Observation Of Bone Tissuementioning
confidence: 99%
“…Milk and dairy products are a valuable source of minerals, including calcium and phosphorus, high-quality proteins, and essential vitamins. They contain functional ingredients such as oligosaccharides and exosomes that promote bone growth and development and are also good carriers of probiotics (Jia et al, 2023;Kim et al, 2023;Rizzoli & Biver, 2020). It is worth noting that milk is included in the dietary guidelines for the prevention and treatment of osteoporosis in many countries (Huth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%